A comparative study of non-viral gene delivery techniques to human adipose-derived mesenchymal stem cell - Abdul Halim, Nur Shuhaidatul Sarmiza; Shaik Fakiruddin, Kamal; Ali, Syed Atif; Yahaya, Badrul Hisham (MDPI, 2014)
Mesenchymal stem cells (MSCs) hold tremendous potential for therapeutic use in stem cell-based gene therapy. Ex vivo genetic modification of MSCs with beneficial genes of interest is a prerequisite for successful use of stem cell-based therapeutic applications. However, genetic manipulation of MSCs is challenging because they are resistant to commonly used methods to introduce exogenous DNA or RNA. Herein we compared the effectiveness of several techniques (classic calcium phosphate precipitation, cationic polymer, and standard electroporation) with that of microporation technology to introduce the plasmid encoding for angiopoietin-1 (ANGPT-1) and enhanced green fluorescent protein (eGFP) into human adipose-derived MSCs (hAD-MSCs). The microporation technique had a higher transfection efficiency, with up to 50% of the viable hAD-MSCs being transfected, compared to the other transfection techniques, for which less than 1% of cells were positive for eGFP expression following transfection. The capability of cells to proliferate and differentiate into three major lineages (chondrocytes, adipocytes, and osteocytes) was found to be independent of the technique used for transfection. These results show that the microporation technique is superior to the others in terms of its ability to transfect hAD-MSCs without affecting their proliferation and differentiation capabilities. Therefore, this study provides a foundation for the selection of techniques when using ex vivo gene manipulation for cell-based gene therapy with MSCs as the vehicle for gene delivery.